Vaginoscopy in perpubertal girls - Corimanya, Juan (2015)
Objectives: To determine prepubertal girls’ gynecologic pathologies by using vaginoscope for diagnosis. Design: Descriptive, retrospective, transversal study. Setting: Gynecology Service, Instituto Nacional de Salud del Niño, Lima, Peru. Participants: Prepubertal girls. Interventions: During the period 2000-2007, 32 prepubertal girls were subjected to vaginoscopy for diagnosis or treatment of gynecological diseases. Main outcome measures: Correlation of vaginoscopy and gynecologic pathologies. Results: Most frequent gynecologic pathologies were chronic vulvovaginitis in 23 cases (71,9%), vaginal bleeding in 3 cases (9,4%), rectovaginal fistula in 2 (6,3%), child abuse, tumor vaginal, cervical dysplasia and low placed cloaca. Postoperative diagnoses were chronic vulvovaginitis (40,6%), vaginitis and cervicitis (34,4%), vaginal septum and rectovaginal fistula, vulvovaginitis and sequel of genital trauma, germ cell tumor, sarcoma botrioides, vaginal polyp, foreign body in vagina, cervical dysplasia and normal vagina. Average operative time was 23 minutes and time of general anesthesia 39 minutes; most patients were discharged in good condition and only 3 remained hospitalized (9,4%). Conclusions: Vaginoscopy under anesthesia in prepubertal girls allowed diagnosis of various gynecological diseases with safety.